JOURNEYS ACROSS SOUND. - WONG, PAMELA (ArtAsiaPacific)
An interview with Tarek Atoui, the artist is presented. He discusses his journey from Beirut to France, where he deepened his understanding of electronic music and developed a passion for math and science, which influenced his experimental sound work. He also talks about his shift from DJing to creating experimental sound compositions, mentioning his influences and the importance of physicality in his work and reflects on the creation of "Un-drum: Strategies of surviving noise,"